Reseña/Review (Muriel, Daniel y Crawford,Garry, "Video Games as culture. Considering the Role and Importance of Video Games in Contemporary Society", London: Routledge, ISBN: 9781138655119, págs. 194, 2018) - Moreno Azqueta, Carlos (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2019)
Reseña/Review (Muriel, Daniel y Crawford,Garry, "Video Games as culture. Considering the Role and Importance of Video Games in Contemporary Society", London: Routledge, ISBN: 9781138655119, págs. 194, 2018)